Grafične pripovedi in pripovednost - Flis, Leonora (Primerjalna književnost, 2020)
The article focuses on the narrative principles of graphic narratives representing a hybrid genre that dwells at the intersection of literary and visual storytelling. The genre's multimodality is also viewed through the prism of certain principles of postclassical narratology. Graphic narratives occupy the intersection of showing and telling stories; they always tell a story, so they are a narrative genre. Graphic storytelling enables us to pose some fundamental questions that concern, for example, the temporal aspect of narrativity (understood as a collection of formal and contextual traits that define a narrative) and the issue of focalization. Graphic narratives treat time somewhat differently from (merely) verbal narratives, as a sense of time is created through the relationship between the visual and the verbal. Moreover, apart from the (mostly) framed images, graphic narratives also contain the so called "gutter" or an empty space between the frames. Scott McCloud, himself a comics theorist and comics artist, says that gutter is the place where the illusion of the movement of space and time takes place. Using the examples from a few graphic narratives (by Art Spiegelman, Joe Sacco, and Marjane Satrapi), the article shows the specifics of graphic storytelling, which, with its sequential nature, the principles of montage, the composition of individual pages, and other structural characteristics, enables the formation of narratives. When we talk about graphic narratives, it is appropriate to talk about the transgeneric and transmedial narratology, hence the article also exposes the role of postclassical narratology in the process of interpreting and understanding graphic narratives.
Keywords: grafična pripoved; grafični roman; graphic narrative; graphic novel; hibridni žanri; hybrid genres; narativnost; narrativity; postclassical narratology; postklasična naratologija; roman v stripu; Sacco, Joe; Satrapi, Marjane; Spiegelman, Art